Evaluating the physiological responses to treadmill exercise based on the 6-minute walk test in individuals with COPD across severity levels - Shaphe, Mohammad Abu; Alshehri, Mohammed M.; Alajam, Ramzi Abdu; Ghazwani, Ahmed; Temehy, Basema Fathi; Sahely, Ahmad; Husein J Alfaifi, Bsmah; Hakamy, Ali; Khan, Ashfaque; Aafreen, Aafreen; Khan, Abdur Raheem (Frontiers in Physiology, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) limits exercise capacity and impacts lifestyle. While treadmill exercise aids rehabilitation, the 6-Minute Walk Test (6 MWT) serves as a vital assessment tool. The study examines whether physiological outcomes differ across COPD severities using the 6 MWT.ObjectivesTo compare physiological responses during treadmill exercise, based on 6 MWT results, across COPD severity levels per Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria.MethodsA cross-sectional study involved COPD patients classified by 2023 GOLD standards from Jazan University Hospital Saudi Arabia. Of 40 initial participants, 35 were retained, excluding those with recent complications. Cardiopulmonary function was assessed by measuring heart rate and blood pressure with an automated monitor, while respiratory parameters were evaluated using a spirometer, all in accordance with the guidelines set by the American Thoracic Society.Results35 participants (87.5%), aged 40–75 years (mean 58.3 ± 9.8), completed the study, with 23:12 males to females. Participants averaged 382 ± 65 m in 6 MWT and 17 ± 5 min on treadmill. Forced expiratory volume (FEV1) showed strong correlation (r = 0.99) between exercises. ANOVA revealed significant heart rate differences across COPD severities (p = 0.0001). Paired t-tests showed differences in heart rate, oxygen saturation (SpO2), and respiratory rate between modalities (p < 0.05).ConclusionThe 6 MWT and treadmill exercise elicit distinct physiological responses in COPD patients, with disease severity affecting heart rate variations. These findings suggest 6 MWT may not directly predict treadmill exercise responses, emphasizing the need for tailored exercise prescriptions.